Automatic calculation of personal body segment parameters with a microsoft kinect device - Chiu, C.-Y.; Fawkner, S.; Coleman, S.; Sanders, R. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to introduce an automatic method for calculating personal body segment parameters (BSPs). In this automatic method, a Microsoft Kinect device was used to capture depth frames for measuring joint locations. The open source software, MakeHuman, was used for generating 3D human models by referring using the joint location data captured from the depth frames. Segmental meshes were obtained from the generated 3D human models and personal BSPs could be calculated automatically. The tests showed that the developed method can complete all of the processes without manual digitizing, anatomical landmark detection and medical scanner operation. Further research should be conducted to establish the accuracy of the segmental masses, centres of mass and moments of inertia acquired from the developed methods.